Hypomethylation of 111 Probes Predicts Poor Prognosis for Glioblastoma - Chen, Qi; Zhao, Min; Yin, Chengliang; Feng, Shiyu; Hu, Jian; Zhang, Qiang; Ma, Xiaodong; Xue, Wanguo; Shi, Jinlong (Frontiers in Neuroscience, 2019)
Glioblastoma is a complicated brain tumor with heterogeneous outcome. Identification of effective biomarkers is an urgent need for the treatment decision-making and precise evaluation of prognosis. Based on a relatively large dataset of genome-wide methylation (138 patients), a joint-score of 111 methyl-probes was found to be of statistical significance for prognostic evaluation. Low joint-score were significantly associated with adverse outcomes (OS: P < 0.001). Multivariable analyses adjusted for known risk factors confirmed the low joint-score of 111 methyl-probes as a high risk factor. The prognostic value of joint-score was further validated in another dataset of glioblastoma patients (OS: P = 0.006). Additionally, variance analysis revealed that aberrant genetic and epigenetic alterations were significantly associated with the joint-score of those methyl-probes. In conclusion, our results supported the joint-score of 111 methyl-probes as a potential prognosticator for the precision treatment of glioblastoma.